THE THE INFLUENCE OF TECHNICAL ANALYSIS, RELATIVE STRENGTH INDEX (RSI) AND MOVING AVERAGE (MA) ON STOCK PURCHASE DECISIONS : Case Study on The Sharia Capital Market in Bengkulu City - Mulya Rasyid, Leonardo Duarsie; Setiawan, Romi Adetio; Polindi, Miko (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Sharia capital markets have developed in various countries, each with its own unique investment characteristics. In this context, stock investment decisions in the Sharia capital market can be influenced by various factors. The objective of this study is to determine the effect of technical analysis (X1), the relative strength index (X2), and the moving average (X3) on stock purchase decisions (Y) in the Sharia capital market in Bengkulu City. To test this, the study used a quantitative method with primary data collection techniques in the form of questionnaires distributed to 100 respondents. The data analysis technique used was multiple linear regression using SPSS version 25.0. From the results of the research and discussion, it was found that technical analysis, relative strength index and moving average influenced stock purchasing decisions as indicated by the results of the T test, namely, technical analysis t-count value > t-table (2.115 > 1.660), relative strength index t-count value > t-table (5.600 > 1.660), moving average t-count value > t-table (4.537 > 1660), based on the results of the F test, the results obtained were 65.9% of stock purchasing decisions were influenced by these three factors while 34.1% were determined by other factors.